Evaluación del efecto de Filgrastim en relación a la Serie Roja y Serie Blanca en la Calidad Seminal en el Canino Doméstico (canis familiaris) - Latacunga Cuchipe, Nataly Margarita (2018)
Animal research has always been directed at animal production for human consumption. However, the present study is carried out to promote research on topics related to new biomedical treatments in pets; explorable in human medicine. The principal purpose of this study was to analyze the effect of Filgrastim® (r-Met-Hu-G-CSF) in relation to the hematological values (red series and white series) and its incidence in the parameters of seminal quality (motility, volume and sperm concentration) of the domestic canine. The reseaechers worked with 10 canines, 5 animals distributed in the control group and 5 animals in the treatment group, from an age of 6 months to 1 year, of medium size and male sex which were applied at a dose of 5mcg each 24 hours for 4 consecutive days subcutaneously; In addition, blood samples were taken before and after each application for blood and hormonal assessment (testosterone), as well as semen samples for evaluation of seminal motility parameters, and sperm concentration. For the statistical analysis, the T students test was used for two related and unequal samples. Therefore, it is concluded that in this study the obtaining of hematopoietic stem cells in the domestic canine related to the white series was satisfactory, observing that the greater mobilization of stem cells (immature) was presented in the T1 treatments regarding the control group and its impact on seminal quality. Consequently, the indices of the parameters of the white series (leukocytes, lymphocytes, monocytes and granulocytes) presented significant numerical changes in contrast to the control group. While the values of the red series (erythrocytes and platelets) did not show significant changes in the numerical values, determining a positive and negative correlation between both series, there was also direct influence of Filgrastim® (5mcg / kg), improving the motility and concentration sperm in the domestic canine.